The Concept of Aqidah Akhlak Education Curriculum in Forming Istiqamah Character of Elementary School Students - Lidyawati, Reky; Asrori, Mohammad; Mahmudi, Zaenul; Barizi, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
There is a need for an aqidah akhlak education curriculum that can shape the character of istiqamah students at the elementary school level as a basic foundation for good character building. Thus, this research seeks to explore: (1) How is the concept of aqidah akhlak education curriculum in shaping the istiqamah character of elementary school students at the stage of learning planning, learning implementation, and learning evaluation? (2) How is implementing the aqidah akhlak education curriculum in shaping the istiqamah character of elementary school students at the stage of learning planning, learning implementation, and learning evaluation? This research uses a qualitative approach. This type of multi-site study research is chosen to provide a search for the proposed research problem. Data collection techniques were carried out by 1) in-depth interviews, 2) participant observation, and 3) documentation. The data were analyzed with an interactive model consisting of data condensation, data display, conclusion, and verification. Data validity checking is based on four criteria: degree of trust (credibility), degree of transferability, degree of dependability, and degree of certainty (confirmability). The results of this study were found (1) the concept of the aqidah akhlak education curriculum in shaping the istiqamah character of elementary school students at the learning planning, learning implementation, and learning evaluation stages in two Islamic elementary schools in Situbondo and (2) implementation of the aqidah akhlak education curriculum in shaping the istiqamah character of elementary school students at the stage of learning planning, learning implementation, and learning evaluation in two Islamic elementary schools in Situbondo.